2019
DOI: 10.1186/s12879-019-4270-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection status and associated factors among a multi-site sample of people who used illicit drugs in the Amazon region

Abstract: Background Elevated rates of Hepatitis C Virus (HCV) infection have been reported in epidemiological studies with people who used illicit drugs (PWUIDs) in different Brazilian regions. In Brazil’s Amazon region, studies have already identified the common use of illicit drugs among adolescents and the high prevalence of HCV infections among PWUIDs. However, all studies done with PWUIDs were conducted with small samples and within limited geographic coverage. This study determined the prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 48 publications
0
21
0
2
Order By: Relevance
“…In the Amazon region, the estimated prevalence of HCV infection ranges from 1% to 3%, with higher rates being recorded in vulnerable groups, such as PWUDs (23.1%), patients undergoing hemodialysis (8.4%), and patients with hemophilia (48.4%) [5,[20][21][22][23][24]29,36,46]. The prevalence of HCV infection detected in this study was 10.7%, and most of these infections were classified as active (7.8%).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In the Amazon region, the estimated prevalence of HCV infection ranges from 1% to 3%, with higher rates being recorded in vulnerable groups, such as PWUDs (23.1%), patients undergoing hemodialysis (8.4%), and patients with hemophilia (48.4%) [5,[20][21][22][23][24]29,36,46]. The prevalence of HCV infection detected in this study was 10.7%, and most of these infections were classified as active (7.8%).…”
Section: Discussionmentioning
confidence: 66%
“…In this study, there was a predominance of genotype 1 (81.3%), especially subtypes 1a (34.4%) and 1b (46.9%), with the presence of RASs in antiviral therapy-naive FSWs. Historically, epidemiological studies conducted in the Amazon region have indicated the predominance of HCV genotype 1 but without an evaluation of the presence of RASs [5,18,20,36]. Studies conducted in other Brazilian regions reported the presence of genetic variants in chronic HCV-infected patients and not treated with DAAs, which may vary from 3.2% to 18.9% [19,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is one of the first epidemiological reports on syphilis in FSWs in the Brazilian Amazon region. In this region, the Amazon rainforest occupies large areas of the northern Brazil, which causes relative isolation, resulting (or because of) limited infrastructure and public services and low human development [11]. This scenario has a negative impact on sexual behaviour, increasing risk-taking activities [12][13][14].…”
Section: Discussionmentioning
confidence: 99%